2015
DOI: 10.1063/1.4905496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the surroundings and conformerisation ofn-dodecane molecules on evaporation/condensation processes

Abstract: The evaporation/condensation coefficient () and the evaporation rate () for n-dodecane vs. temperature, gas pressure, gas and liquid density, and solvation effects at a droplet surface are analysed using quantum chemical DFT calculations of several ensembles of conformers of ndodecane molecules in the gas phase (hybrid functional ωB97X-D with the cc-pVTZ and cc-pVDZ basis sets) and in liquid phase (solvation method SMD/ωB97X-D). It is shown that  depends more strongly on a number of neighbouring molecules i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…To obtain the values of this coefficient, using this analysis, one would need to repeat these calculations for a wide range of angles of attack, orientation of molecules and energies for various conformers and various conditions of clusters and nanodroplets. Since this is not currently feasible, an alternative approach to calculating this coefficient, taking into account quantum chemical effects, is described in the next section, following [11,7].…”
Section: Interaction Between Molecules and Dropletsmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain the values of this coefficient, using this analysis, one would need to repeat these calculations for a wide range of angles of attack, orientation of molecules and energies for various conformers and various conditions of clusters and nanodroplets. Since this is not currently feasible, an alternative approach to calculating this coefficient, taking into account quantum chemical effects, is described in the next section, following [11,7].…”
Section: Interaction Between Molecules and Dropletsmentioning
confidence: 99%
“…It was shown that the most accurate expression for the condensation coefficient (assumed to be equal to the evaporation coefficient) is the one averaged over the states of various conformers transferred between two phases. This was given by the following formula [11]:…”
Section: Evaporation/condensation Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a novel hybrid method of the quantum transition state theory and classical kinetic gas theory (QTST-CKGT) could make this connection in a new way without requiring the evaporation/condensation coefficient [3,4]. In Reference [1], it was assumed that the evaporation of n-dodecane is an enthalpic process with no entropy change in the temperature range of 298.15-648.15 K, as well as no energy barrier over the interfacial layers. However, recently the basis of the entropy-enthalpy competition mechanism [2] and the importance of confinement effects alongside the molecular conformational changes at the interface [3,4] were established during the evaporation/condensation process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a model was developed by Gun'ko et al [1] to estimate the evaporation/condensation coefficient (β) and evaporation rate (k) of n-dodecane based on the quantum mechanics solvation model SMD and the Gibbs free energy of evaporation (∆G ev (T)). SMD is based on the solute electron density, the dielectric constant, and the atomic surface tension [2].…”
Section: Introductionmentioning
confidence: 99%